2019
DOI: 10.1088/1555-6611/aaffc4
|View full text |Cite
|
Sign up to set email alerts
|

2 µm vector mode-locked pulses from Tm:Y2O3 ceramics laser

Abstract: We report on stable passively mode-locked (ML) pulses with Tm:Y 2 O 3 ceramics operating at a 2 µm wavelength range for the first time. With a SESAM, synchronous ML pulses with dual-wavelengths are obtained, with a typical pulse width of 40 ps, a maximum output average power of 240 mW and a pulse repetition rate of ~124 MHz. The output pulses were further proved to be stable polarization-locked vector pulses. To our knowledge, this is also the first observation of vector pulses in 2 µm ML solid-state oscillato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…[7][8][9] In particular, compared with other laser media, the distinct advantage of the Y 2 O 3 crystal is its good thermostability that can ensure the stability of the pumping process using laser diodes. The renaissance of Tm 3+ doped Y 2 O 3 (Y 2 O 3 :Tm 3+ ) laser materials has spontaneously attracted significant attention and many reports 10 have demonstrated that passively mode-locked pulses of Y 2 O 3 :Tm 3+ occur at 2 mm. The first attempt to prepare the Y 2 O 3 :Tm 3+ laser was made in 1964 by Barnes et al 11 Subsequently, Gruber et al 12 recorded the optical fluorescence and absorption spectra of Y 2 O 3 :Tm 3+ and identified the main 4f 12 electronic energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In particular, compared with other laser media, the distinct advantage of the Y 2 O 3 crystal is its good thermostability that can ensure the stability of the pumping process using laser diodes. The renaissance of Tm 3+ doped Y 2 O 3 (Y 2 O 3 :Tm 3+ ) laser materials has spontaneously attracted significant attention and many reports 10 have demonstrated that passively mode-locked pulses of Y 2 O 3 :Tm 3+ occur at 2 mm. The first attempt to prepare the Y 2 O 3 :Tm 3+ laser was made in 1964 by Barnes et al 11 Subsequently, Gruber et al 12 recorded the optical fluorescence and absorption spectra of Y 2 O 3 :Tm 3+ and identified the main 4f 12 electronic energy levels.…”
Section: Introductionmentioning
confidence: 99%